A Molecular Modeling Study of Oleate Monolayers Adsorbed at Calcium Mineral Surfaces - Beena Rai; Pradip (International Mineral Processing Congress, 2003)
A molecular modeling study was carried out on an adsorbed oleate monolayer on the surfaces of three calcium minerals, fluorite, calcite and fluorapatite using Universal Force Field (UFF) potentials. The cleavage plane of calcite {104} was the best template for oleate monolayer adsorbed since the surface structure enabled all the calcium sites available on the surface to be occupied by oleate anions. The area occupied per chain of oleate in this well packed monolayer was computed to be 20.2 Å, which exactly matches the value calculated to be the parking area per oleate molecule for a fully packed monolayer based on strictly geometric calculations. On the other hand, the precentage of calcium sites occupied by oleate to achieve a fully packed monolayer in case of fluroite and and fluorapatite was found to be 67% and 75% respectively. The results of this theoretical study suggest that while all the three adsorption conformations, that is unidentate, bidentate and bridging type are equally likely on fluorite and fluorapatite, bridging is most likely on calcite. Interestingly, all the conformations are observed experimentally for calcite-oleate system also. The reasons for this discrepancy between the theoretical predictions and experimental observations are not clear. More work is required to resolve this discrepancy, in particular simulation studies in presence of solvent water molecules on the surface.